Analisis Kualitas Air dan Status Mutu Serta Beban Pencemaran Sungai Mahap di Kabupaten Sekadau Kalimantan Barat - Ranty Christiana; Ika Muthya Anggraini; Hezliana Syahwanti (Jurnal Serambi Engineering, 2020)
Sungai Mahap is used by the people of Nanga Mahap Village, Nanga Mahap District, Sekadau Regency for daily needs such as cooking, transportation and even consumption as drinking water. Utilization is done by the community because this area has not been flooded with clean water facilities. The quality and status of the Mahap River water quality standard needs to be further examined to study the feasibility of water as an air source used by the community regarding the importance of increasing plantation activities upstream. This research uses descriptive method using quantitative. Air sampling was conducted using a sample survey method with proposed parameters namely BOD, COD, pH, DO, TSS and NH3. Water quality testing is based on Government Regulation No. 82 of 2001 and determines the status of water quality using the STORET method and the pollution index based on the Decree of the Minister of Environment No.115 of 2003. In this study, the river pollution load was also calculated. The results show that the composition of BOD, COD, and Fe has exceeded the specified quality standards. The water quality status of the Mahap River is classified as moderate to severe based on the STORET method and Pollution Index. The highest river pollution load occurs at point II, in the dry season at 104.725 kg/day and in the rainy season at 171.873 kg/day